Financial Well-Being: The Mediating Effect of Financial Behavior on The Relationship Between Islamic Financial Literacy and Financial Attitudes - Helmalia, Helmalia; Putri, Mela Emelya; Mawaddah, Arini Alfa; Putra, Romy Yunika; Ifriadi, Rike (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2025)
Purpose:Understanding the factors that influence financial well-being is important for promoting financial sustainability, especially amid economic uncertainty that requires effective and planned management. Such financial management requires adequate Islamic financial literacy, positive financial attitudes, and appropriate financial behavior.Design/Methodology:This study investigates the mediating role of financial behavior in the relationship between Islamic financial literacy, financial attitudes, and financial well-being. Using a quantitative design, data were collected from 100 civil servant teachers in Agam Regency, Indonesia, through a structured questionnaire. The sample was determined using the Slovin formula and selected through simple random sampling. Partial Least Squares Structural Equation Modeling PLS-SEM 4 was used for data analysis.Findings:The findings show that Islamic financial literacy does not directly affect financial well-being but indirectly through financial behavior. Financial attitudes have a significant direct influence on financial well-being, while their indirect influence through financial behavior is not supported. These results underscore the important role of financial behavior as a mechanism linking financial knowledge to better financial outcomes.Practical Implications:This study offers meaningful implications for financial education programs and policy interventions focused on developing long-term financial resilience.Originality/Value:This study offers a novel perspective on understanding financial well-being by positioning Islamic financial literacy as a foundational approach. It not only addresses the limitations of previous research that primarily focused on conventional financial literacy, but also provides a more contextually relevant understanding for communities that manage their finances based on Sharia principles.